INTERAKSI PELAKU DAUR ULANG SAMPAH MELALUI UJI REGRESI LINEAR DI KELURAHAN PANGGUNG LOR, KUNINGAN DAN BANDAR HARJO KOTA SEMARANG - Maryono, Maryono; Andriyani, Riki (Universitas Diponegoro, 2010)
Recycling process and activities are part of the solid waste management. Informal Actor such as Scavengers, Small Middleman and Big Middleman has a unique networking. The interaction can beclassified as node, subpoint and centerpoint. They has a relationships which representation of solid waste transport among area and region. Based on Sejati research (2009), the networking and relationships among the informal actor of Recycling process like can be astimated as a mathematic model. Regrestion analysis was running to test the mathematic model. Panggung Lor, Bandarharjo and Kuningan, at Semarang was chosen as location study because of the characteristic of the Recycling activities.